2020
DOI: 10.1016/j.jlumin.2020.117092
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the photoluminescence decay kinetics in metal halide perovskite nanocrystals and thin polycrystalline films

Abstract: One of distinguishing features of metal halide perovskites is their long (up to microseconds) photoluminescence (PL) lifetimes, which are regularly observed for this class of semiconductors in spite of their direct gap origin. It is difficult to explain this contradiction in the framework of usual two-level Jablonski photophysical diagram because the absorption coefficient (i.e., the oscillator strength of the direct optical transition) is too high in perovskites to hold such long PL lifetimes. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 60 publications
6
30
0
Order By: Relevance
“…The PL decay profile of 100% PLQYs does not exhibit single-exponential decay behavior, a fact that could be explained by the trapping detrapping-processes with shallow defects in the perovskite conduction band, as it has been previously reported. 60 Accordingly, we suggest that Sr modification also plays a main role in the recombination kinetics of PQDs. Yao et al reported that Sr 2+ can provide radiative energy levels near or into the conduction band (CB) states from CsPbI 3 QDs.…”
Section: Analysis and Discussionmentioning
confidence: 81%
“…The PL decay profile of 100% PLQYs does not exhibit single-exponential decay behavior, a fact that could be explained by the trapping detrapping-processes with shallow defects in the perovskite conduction band, as it has been previously reported. 60 Accordingly, we suggest that Sr modification also plays a main role in the recombination kinetics of PQDs. Yao et al reported that Sr 2+ can provide radiative energy levels near or into the conduction band (CB) states from CsPbI 3 QDs.…”
Section: Analysis and Discussionmentioning
confidence: 81%
“…The radiative recombination rate corroborates the previous values reported in the literature, [ 39,45,46 ] and the two trapping rates are also within the range expected based on numerous studies. [ 30,39,40 ] These findings indicate that trapping into the shallow trap states is relatively fast and can fully explain the difference observed between the TA and FLUPS signals. Second, the energy difference Δ E between S and X 1 states is small (<k B T ), as expected.…”
Section: Figurementioning
confidence: 74%
“…This may explain the extended PL lifetimes that have been reported previously in the literature. [ 39,40,47 ] Additionally, we have also demonstrated the importance of capping ligands to prevent the formation of deep trap states. Desorption of the ligand from the surface due to sample aging increases the number of deep trap states and directly influences the PLQY of the NPls.…”
Section: Figurementioning
confidence: 89%
See 1 more Smart Citation
“…The TRPL and TRMC measurements were carried out with different light intensities, both being significantly smaller than 1 sun, where carrier dynamics are dominated by trapping processes, which can make direct comparison of these two techniques difficult. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%